Epstein–Barr virus EBER1 and murine gammaherpesvirus TMER4 share conserved in vivo function to promote B cell egress and dissemination - Hoffman, Brett A.; Wang, Yiping; Feldman, Emily R.; Tibbetts, Scott A. (Proceedings of the National Academy of Sciences - PNAS, 2019)
The oncogenic gammaherpesviruses, including human Epstein–Barr virus (EBV), human Kaposi’s sarcoma-associated herpesvirus (KSHV), and murine gammaherpesvirus 68 (MHV68, γHV68, MuHV-4) establish life-long latency in circulating B cells. The precise determinants that mediate in vivo gammaherpesvirus latency and tumorigenesis remain unclear. The EBV-encoded RNAs (EBERs) are among the first noncoding RNAs ever identified and have been the subject of decades of studies; however, their biological roles during in vivo infection remain unknown. Herein, we use a series of refined virus mutants to define the active isoform of MHV68 noncoding RNA TMER4 and demonstrate that EBV EBER1 functionally conserves this activity in vivo to promote egress of infected B cells from lymph nodes into peripheral circulation.